Riba Konsumtif di Era PayLater: Kajian Al-Qur’an dan Hadis sebagai Hakam atas Kredit Barang Konsumen Berbunga - Permana, Angga; Jiddan, Adam Mustaqim; Nazib, Azlan; Fadhillah, Fauzan Fahd; Al Ayubi, Sholahuddin; Marjuki, Akhmad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
The purpose of this study is to examine PayLater practices from a historical perspective as a response to consumer credit transactions that are common in the digital age. The main finding of this study is that more and more people, especially members of Generation Z and Millennials, are using PayLater services, raising ethical concerns regarding the existence of fixed and progressive interest rates. Through a qualitative approach with a case study design, this study analyzes textual analyses of usury from primary sources such as Kutub al-Sittah, Bulugh al-Maram, and Riyadh al-Salihin. This analysis is then compared with PayLater practices used by popular e-commerce platforms in Indonesia, including Shopee, Gojek, and Akulaku. Data was collected through a study of hadith literature, fiqh muamalah, DSN-MUI fatwas, OJK regulations, and analysis of digital documents from service providers. The study findings show that PayLater practices contain elements of riba nasiah, which is debt arising from payment terms described in detail in the Qur'an (QS. Al-Baqarah: 275–279) and the hadith of the Prophet. Additionally, interest and late fees in this system contradict the principles of fairness, transparency, and the prohibition of additional debt in muamalah fiqh, thus failing to meet Sharia contract standards. This study concludes that hadith remains relevant as a legal authority in assessing modern digital financial phenomena, and underlines the urgency of redesigning PayLater products based on sharia contracts such as murabahah or ijarah to protect Muslim consumers and uphold maqashid al-syari'ah.